A mixed methods study protocol evaluating early screening, triaging, risk assessment and health optimisation in perioperative pathways - Katie Gilchrist; Bo Hou; James Bedford; Patrick Nyikavaranda; Margaret Ogden; Grainne Brady; Angus I. G. Ramsay; Ramani Moonesinghe; Snehal M. Pinto Pereira; Cecilia Vindrola-Padros (PLoS ONE, 2025)
Background Over 10 million operations are carried out every year in the UK, improving millions of lives. While most operations are low-risk, some result in patients having poor outcomes. Preoperative assessment evaluates a patient’s health prior to surgery to identify risks and where possible minimise them through optimisation. However, this preoperative assessment often takes place close to the planned date of surgery, meaning there is little time to optimise patients’ health. Early preoperative screening is the process of evaluating a patient’s health earlier in the surgical pathway. In 2023, NHS England introduced a new programme where all hospitals were to implement early screening, triaging, risk assessment and health optimisation with the aim of increasing safety through reduced perioperative complications, increased efficiency (e.g., through reductions in last-minute cancellations), reductions in length of hospital stay, and identifying people who can undergo surgery without requiring an overnight stay. Here we describe the protocol to examine the implementation and impact of this new programme. Methods A mixed methods research design will be used to evaluate this new programme. We will conduct a formative implementation evaluation using rapid qualitative methods consisting of interviews with staff members and patients across three broadly representative specialities (colorectal cancer surgery, repair of abdominal aorta and knee replacement) and observations of key meetings held regarding implementation activities. An interrupted time series analysis will address patient centered outcomes (days alive and out of hospital at 30, 180 and 365 days after surgery; postoperative hospital length of stay; emergency re-admission within 30 days) using routinely collected electronic health records. Discussion This study will provide lessons on the barriers and facilitators to implementation and will highlight staff and patient experiences of the new programme. It will also assess impact on patient centred outcomes using routinely collected hospital data and quasi-experimental research methods.